Analysis of Major National Science Center Websites in Taiwan. (March 2014) - Chen, Chia-Hsiang; Ke, Hao-Ren
Abstract : This study employs a content analysis approach to analyze the Websites of four major science centers in Taiwan. The aim is to determine if their Websites meet the criteria of 'Evaluating Science WWW Resources' established by North Carolina State University. The criteria consist of five categories and 29 items. The five categories are: Science Content Issues, Navigation, Website Design, Performance, and Multimedia Issues. The results of this study indicate that the Websites of the four science centers mostly conformed to the criteria, and their e-resources are sufficient for the general public. However, several recommendations are proposed based from the results. In Science Content Issues, a description about the responsible authors including their credentials, emails, and biographical information should be added so that the content can be validated by scientists or professional educators. In Multimedia Issues, Web 2.0 social networks may be added to allow users to share information in real time.*